2000
DOI: 10.1080/026870300401513
|View full text |Cite
|
Sign up to set email alerts
|

Semantic feature analysis as a treatment for aphasic dysnomia: A replication

Abstract: Semantic Feature Analysis (SFA) is a treatment technique designed to improve lexical retrieval by increasing the level of activation within a semantic network. The purpose of this study was to replicate the Boyle and Coelho (1995) study in which SFA was applied with a mild non-¯uent aphasic individual resulting in improved confrontation naming of trained and untrained items but no generalization to connected speech. The present study investigated whether a comparable treatment eåect could be demonstrated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(130 citation statements)
references
References 10 publications
7
114
1
8
Order By: Relevance
“…The results of this study partially concur with previous findings of SFA investigations [20][21][22][23], showing that treatment resulted in positive changes for trained items. However, we found no generalization to naming of untrained actions in this investigation, whereas improvements in untrained object-naming have been reported for all previous SFA participants who demonstrated improvements with trained items.…”
Section: Response Generalization Effectssupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study partially concur with previous findings of SFA investigations [20][21][22][23], showing that treatment resulted in positive changes for trained items. However, we found no generalization to naming of untrained actions in this investigation, whereas improvements in untrained object-naming have been reported for all previous SFA participants who demonstrated improvements with trained items.…”
Section: Response Generalization Effectssupporting
confidence: 83%
“…Additionally, generalization may be facilitated by application of the compensatory strategy of systematically retrieving features, which may serve a self-cueing function. SFA has been demonstrated to result in improved retrieval of trained nouns and has been shown to promote retrieval of untrained nouns [20][21][22][23]. SFA has also been associated with improvements in content production during discourse.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that confrontation naming on trained and untrained stimulus items was significantly improved. The results of this study have shown that SFA treatment is effective in improvement of naming deficits [10,11]. A recent systematic review has also indicated that SFA was an effective treatment for improving confrontational naming in the majority of participants.…”
Section: Introductionmentioning
confidence: 65%
“…However, many of these studies have found little generalization to untrained items. Notably, studies focused on strengthening the semantic attributes of target items have been more successful at facilitating generalization to untrained items (Boyle, 2004;Boyle & Coehlo, 1995;Coehlo, McHugh, & Boyle, 2000;Drew & Thompson, 1999;Kiran & Thompson, 2003a;Lowell, Beeson, & Holland, 1995). Whereas some of these studies have focused on generalization to items within a superordinate category (Drew & Thompson, 1999), others have also observed generalization to items across semantic categories (Boyle, 2004;Boyle & Coehlo, 1995;Coehlo et al, 2000;Lowell et al, 1995).…”
Section: Semantically Based Naming Treatmentmentioning
confidence: 99%